Report of the Commission of Inquiry on Job Security in Oil Companies (Including Refineries) - Planning Commission (Planning Commission, 1969)
Burmah-Shell Oil Storage and Distributing Company of India Limited (Burmah-Shell), Esso Standard Eastern Inc. (Esso) and Caltex (India) Limited (Caltex) are all foreign Oil Companies which, till the advent of the Indian Oil Corporation (IOC), had a dominant share in the storage, marketing and distribution of petroleum products in India. They appear to have enjoyed almost an uninterrupted period of prosperity and expansion till about the beginning of 1964. Even prior to this period, their efficiency measures including their plans of rationalisation and mechanisation of accounting processes and their methods to reduce their employment strength seem to have raised serious apprehensions about security of jobs in the minds of their workers and the Unions.
Ministry of Labour, Employment and Rehabilitation (Department of Labour and Employment) Government of India